Nutritional Characterization of Fruits from Three African Plant Species: Dialium guineense Willd, Parkia biglobosa Jacq. and Andansonia digitata L. - Manuela Lageiro; Jaime Fernandes; Ana C. Marques; Manuela Simões; Ana Rita F. Coelho (Plants)
Dialium guineense (velvet tamarind), Parkia biglobosa Jacq. (African locust bean) and Adanosonia digitata L. (baobab) are fruits from African plants whose nutritional potential remains poorly characterised. As such, their pulps and seeds were analysed for colour (CIELab system), moisture, ash, protein, fat, soluble and insoluble dietary fibre, free sugars (HPLC-RI), organic acids (HPLC-PDA), macro and microelements (XRF analyser) and amygdalin (HPLC-PDA). The colours of their pulps differed considerable (ΔE > 38 between the velvet tamarind and African locust bean) and the moisture content was lower in seeds (about 7%) compared to pulps (9–13%). Seeds were more concentrated in protein (20–28%) and fat (5–22%), whereas pulps were richer in sugar (1–12%). African locust bean pulp was the sweetest (39% total sugar), while baobab pulp contained the highest soluble fibre (>30%) and citric acid (3.2%), and velvet tamarind pulp was distinguished by its tartaric acid content (3.4%). Seeds of the African fruits presented higher Ca, P, S and Fe contents, whereas pulps had higher K content. No amygdalin (<6.34 mg per 100 g of dry weight) or toxic heavy metal contents were detected. The PCA segregated samples by pulp and seed and the PC1 explains the sugar and moisture of the pulps, while protein, fat and minerals are associated with the seeds. These data confirm that African fruit pulps and seeds have distinct functional profiles, are safe for food use and can be consumed, which is important for efforts to promote the conservation of these tropical plant species.